INTERFERENSI BAHASA MELAYU PONTIANAK TERHADAP BAHASA INDONESIA PADA NAMA-NAMA KELURAHAN DI KOTA PONTIANAK - indah, Nur; Muzammi, Ahmad Rabiul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to describe the forms of interference that found in the names of villages in Pontianak and explain the factors that influence the occurrence of interference in the names of villages in Pontianak. The results in the form of interference can be juxtaposed through the implications in Indonesian Language Learning for SMA X grade 2 semester 2 of 2013 curriculum with basic competency (KD) 3.13 Analyzing the debate on issues, points of view and arguments of several parties and conclusions 4.13 Developing problems / issues from various points of view that are complemented argument in arguing.In the method and technique of providing data using the method of observation that is collecting data by observing objects. Methods and data analysis techniques use the method of matching and the method of agitation, and the method of presenting data analysis using formal methods such as symbols.Based on the results of the data analysis that found 22 names of villages in Pontianak experienced the interference. There are three forms of interference, namely phonological interference, elemental interference and factors that cause interference. So this research can be concluded that interference occurs at the level of community mastery in Indonesian language which relatively low and Pontianak Malay language is still very strong in both language and speech.Keywords: Interference, Pontianak Malay Language, Indonesian Language, Village Names